Prefabricated Building Components as an Alternative to Cast in Place Concrete Projects in Kabul Afghanistan - FORMULI, MOHAMMAD SHARIF HAYAT (İstanbul Kültür Üniversitesi, 2022)
Most of the construction activities in Kabul Afghanistan take place by the conventional method of construction, but currently, there is a huge demand housing in Kabul Afghanistan. Some experts claim that one of the best and fastest methods to build housing for population is prefabricate constructions. Prefabricated concrete structures can be designed in a factory and then installed on construction sites. In this study, the factors influencing the perceptions of experts in considering prefabricated concrete structures as an alternative to the conventional construction materials in Kabul Afghanistan, is examined for the industrialization of public and residential buildings projects. In total 164 valid questionnaires were collected through Google Form from experts in construction sector in Kabul Afghanistan, and the survey outputs are analyzed through SPSS 28 software. To examine the suggested hypotheses, descriptive analysis, principle component analysis, reliability analysis, regression and correlation analysis were performed. Based on the numerical findings and regression analysis, it is observed that there are three key factors affecting the opinions of experts on prefabricated concrete structures, prefabricated concrete can be built in a short time, the cost of prefabricated building is lower than cost of cast in place materials, and management for prefabricating buildings are easier according to quality, production and implementation on site.
Kabil Afganistan'da Yer Beton Projelerine Alternatif Olarak Prefabrik Yapı Bileşenleri
▪ Yüksek lisans tezi.
Keywords: Principal Components Analysis